2020
DOI: 10.1101/2020.01.07.896977
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mono-ADP-ribosylation by ARTD10 restricts Chikungunya virus replication by interfering with the proteolytic activity of nsP2

Abstract: 24 A subset of intracellular mono-ADP-ribosyltransferases diphtheria toxin-like (ARTDs, aka 25 mono-PARPs) is induced by type I interferons. Some of these mono-ARTDs feature antiviral 26 activity while certain RNA viruses, including Chikungunya virus (CHIKV), encode mono-ADP-27 ribosylhydrolases, suggesting a role for mono-ADP-ribosylation (MARylation) in host-virus 28 conflicts. CHIKV expresses four non-structural proteins (nsP1-nsP4), with nsP3 containing a 29 macrodomain that hydrolyzes and thereby reverses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…More recently, it was shown that mutations V33E and D10A of the CHIKV macrodomain, which likely impair both ADP-ribose binding and hydrolysis [9,25], affected polyprotein processing by the nsP2 protease. In vitro, it was shown that the protease could be ADP-ribosylated by PARP10, that protease activity was altered by ADP-ribosylation, and that the macrodomain could reverse this modification [33]. It will be of great interest to determine if nsP2 is ADP-ribosylated during infection.…”
Section: Alphavirusesmentioning
confidence: 99%
“…More recently, it was shown that mutations V33E and D10A of the CHIKV macrodomain, which likely impair both ADP-ribose binding and hydrolysis [9,25], affected polyprotein processing by the nsP2 protease. In vitro, it was shown that the protease could be ADP-ribosylated by PARP10, that protease activity was altered by ADP-ribosylation, and that the macrodomain could reverse this modification [33]. It will be of great interest to determine if nsP2 is ADP-ribosylated during infection.…”
Section: Alphavirusesmentioning
confidence: 99%
“…For example, MARylation of G3BP1, a major SG component, was lost upon overexpression of CHIKV nsp3 (71). Other potential substrates are viral nonstructural proteins, such as the CHIKV nsp2 viral protease, which is MARylated by PARP10 and activated by deMARylation (72).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PARP inhibitors enhance the replication of SARS-CoV and decrease interferon production during infection with a macrodomain mutant virus ( 140 ). Similarly, for CHIKV, the ADP-ribosylhydrolase activity appears essential for viral replication and virulence ( 141 , 142 ). Therefore, the viral macrodomains are thought to play essential roles in infectivity.…”
Section: Reversal Of Dna/rna Adp-ribosylationmentioning
confidence: 99%
“…The NAD + cap blocks efficient translation of RNAs ( 80 ) and the structurally similar ADP-ribose cap could thus impair the translation of viral RNA. A recent study showed that PARP10 overexpression leads to decreased levels of processed viral non-structural proteins in cells ( 142 ), which could be due to impaired processing of the polyprotein as suggested, or due to lower protein translation from a potentially ADP-ribosylated viral RNA. Thus, viral macrodomains may have evolved to antagonize MARylation executed by PARPs that are responsive to interferon signalling.…”
Section: Reversal Of Dna/rna Adp-ribosylationmentioning
confidence: 99%